Extended Criteria Donors in Living Kidney Transplantation Including Donor Age, Smoking, Hypertension and BMI - Plage H; Pielka P; Liefeldt L; Budde K; Ebbing J; Sugünes N; Miller K; Cash H; Bichmann A; Sattler A; Kotsch K; Friedersdorff F (Dove Medical Press, 2020)
Henning Plage,1 Poline Pielka,1 Lutz Liefeldt,2 Klemens Budde,2 Jan Ebbing,3 Nesrin Sugünes,1 Kurt Miller,1 Hannes Cash,1 Anna Bichmann,4 Arne Sattler,5 Katja Kotsch,5 Frank Friedersdorff1 1Department of Urology, Charité – Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin, Humboldt-Universität zu Berlin, Berlin Institute of Health, Berlin, Germany; 2Department of Nephrology, Charité – Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin, Humboldt-Universität zu Berlin, Berlin Institute of Health, Berlin, Germany; 3Department of Urology, University Hospital Basel, Urological University Clinic Basel-Liestal, Basel, Switzerland; 4Department of Anaesthesia and Operative Intensive Care Medicine, Charité –Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin, Humboldt-Universität zu Berlin, Berlin Institute of Health, Berlin, Germany; 5Department of General, Visceral- and Vascular Surgery, Charité –Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin, Humboldt-Universität zu Berlin, Berlin, GermanyCorrespondence: Frank FriedersdorffDepartment of Urology, Charité – Universitätsmedizin Berlin, Corporate Member of Freie Universität Berlin, Humboldt-Universität zu Berlin, Berlin Institute of Health, Charitéplatz 1, Berlin 10117, GermanyTel +49 30 450615219Fax +49 30 450515910Email frank.friedersdorff@charite.dePurpose: An expansion of selection criteria for deceased organ transplantation already exists to manage the current donor shortage. Comparable evaluation of risk factors for living donors should be investigated to improve this issue.Patients and Methods: Our retrospective single-centre study analysed 158 patients with living kidney transplants performed between February 2006 and June 2012. We investigated the influence of donor risk factors (RF) including body mass index over 30 kg/m2, age > 60 years, active nicotine abuse and arterial hypertension on postoperative kidney function with focus on the recipients. This was measured for long-term survival and glomerular filtration rate (GFR) in a 5-year follow-up.Results: Overall, out of 158 living donors, 84 donors were identified to have no risk factors, whereas 74 donors had at least one risk factor. We noted a significant higher delayed graft function (p=0.042) in the first 7 days after transplantation, as well as lower GFR of recipients of allografts with risk factors in the first-year after transplantation. In our long-term results, there was no significant difference in the functional outcome (graft function, recipient and graft survival) between recipients receiving kidneys from donors with no and at least one risk factors. In the adjusted analysis of subgroups of different risk factors, recipients of donors with “age over 60 years” at time of transplantation had a decreased transplant survival (p=0.014).Conclusion: Thus, a careful expansion for selection criteria for living donors with critical evaluation could be possible, but especially the age of the donors could be a limited risk factor.Keywords: living donor nephrectomy, risk factor, selection criteria, survival, GFR